Association of Visceral adiposity Index (VAI) with Glycemic control in Metabolic Syndrome (MetS) (Latakia University Journal -Medical Sciences Series, 2022)
Background: Visceral Adiposity Index (VAI) is suggested as an effective adipose tissue marker that reflects the visceral obesity and the degree of visceral lipid distribution. VAI is strongly associated with glycemic control (HbA1C) in Metabolic Syndrome (MetS) as the most common metabolic abnormalities in Diabetes Mellitus Type II (T2DM). Aims: to evaluate the incidence of MetS in T2DM, and the association of VAI with Glycemic control. The current study was conducted in 129 T2DM (62 male and 67 female) at Tishreen University Hospital and Diabetes Center of Lattakia- Syria during 2020 and 2021. Results: 90 patients (69.77%) were diagnosed with MetS. VAI index increased with severity of MetS in comparison with Body Mass Index (BMI) and Waist Circumference (WC) as overall obesity markers. VAI increased with levels of HbA1C≥8%, (p.value=0.003). VAI was with Cutoff value: (1.9), sensitivity: (70%), specificity: (51%); AUC was the largest compared with WC, BMI. Conclusion: Strong association between VAI as a visceral adipose tissue marker with elevated levels of HbA1C as poor glycemic control in MetS.